CRN13 candidate effectors from plant and animal eukaryotic pathogens are DNA‐binding proteins which trigger host DNA damage response. Issue 2 (24th December 2015) - Ramirez‐Garcés, Diana; Camborde, Laurent; Pel, Michiel J. C.; Jauneau, Alain; Martinez, Yves; Néant, Isabelle; Leclerc, Catherine; Moreau, Marc; Dumas, Bernard; Gaulin, Elodie
Summary: To successfully colonize their host, pathogens produce effectors that can interfere with host cellular processes. Here we investigated the function of CRN13 candidate effectors produced by plant pathogenic oomycetes and detected in the genome of the amphibian pathogenic chytrid fungus Batrachochytrium dendrobatidis (BdCRN13). When expressed in Nicotiana, AeCRN13, from the legume root pathogen Aphanomyces euteiches, increases the susceptibility of the leaves to the oomycete Phytophthora capsici . When transiently expressed in amphibians or plant cells, AeCRN13 and BdCRN13 localize to the cell nuclei, triggering aberrant cell development and eventually causing cell death. Using Förster resonance energy transfer experiments in plant cells, we showed that both CRN13s interact with nuclear DNA and trigger plant DNA damage response (DDR). Mutating key amino acid residues in a predicted HNH‐like endonuclease motif abolished the interaction of AeCRN13 with DNA, the induction of DDR and the enhancement of Nicotiana susceptibility to P. capsici . Finally, H2AX phosphorylation, a marker of DNA damage, and enhanced expression of genes involved in the DDR were observed in A. euteiches ‐infected Medicago truncatula roots. These results show that CRN13 from plant and animal eukaryotic pathogens promotes host susceptibility by targeting nuclear DNA and inducing DDR.